METHODS OF LEVEL BASED TEACHING OF RUSSIAN LANGUAGE AS A NON-NATIVE LANGUAGE - Кublаsheva, Zh. S. (ЗКАТУ им. Жангир хана, 2022)
The article notes that a multilevel approach to teaching Russian as a non-native language allows teachers to establish the learning process according to the competencies that a particular student speaking. Level based teaching of foreign languages has appeared in our domestic methodology and practice of teaching relatively recently in connection with new trends in teaching: a competence-based approach to teaching foreign languages, shifting the focus to individual study of a foreign language by students, the introduction of a point-rating system for evaluating the educational achievements of students.It is noted that the leading technology for teaching the Russian language in modern conditions is communicative learning, which develops all language skills – from speaking and writing to reading and listening. Grammar is mastered in the process of language communication. Active teaching methods are considered: the method of discussion, design, listening, role-playing games - which allows developing the creative abilities of students, developing their thinking and forming their skills necessary for a modern specialist. The transition to multilevel education opens up new horizons in the methodology of teaching Russian as a non-native language, and improves the quality of education.
Кublаsheva , Zh. S. METHODS OF LEVEL BASED TEACHING OF RUSSIAN LANGUAGE / Zh. S. Кublаsheva , Ж. С. Кублашева. - Текст : непосредственный // Ғылым және білім: Қазіргі көзқарас жағдайындағы ғылым мен білімді дамытудың өзекті мәселелері: ХХІІ халықаралық ғылыми-практ. конф. материалдары (12 сәуір 2022 ж.) = Наука и образование: Актуальные вопросы развития науки и образования в условиях современных вызовов: мат. ХХІІ междунар. науч.-практ. конф. (12 апреля 2022 г.) = Science and education: topical issues of the development of sciense and education in the context of modern challenges: mat. of the XXII International Scientific and Practical Conf. (12 aptil 2022). - Уральск: ЗКАТУ им. Жангир хана. - 2022. - № 2 (67) : прил. № 2. - Р. 272-278 (Uralsk).
Keywords: Russian language; level education; competence; foreign language; communicative method; active methods.; зкату; научный журнал